Pengaruh Motivasi Investasi dan Pengetahuan Investasi Terhadap Minat Investasi Mahasiswa Fakultas Ekonomi dan Bisnis di Pasar Modal Melalui Galeri Investasi Universitas Nusa Nipa - Maria Yovita Hasri; Wilhelmina Mitan; Pipit Neken Aurelia (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research aimed to investigate how Investment Motivation and Investment Knowledge affect the Investment Interests of students from the Faculty of Economics and Business in the capital market, using the Investment Gallery of Nusa Nipa University. The study utilized an associative approach with a causal relationship form and a quantitative approach. The population for this study comprised students from the Faculty of Economics and Business of Nusa Nipa University, with a sample size of 94 respondents. The data analysis involved multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) version 23. The research results showed that (1) investment motivation positively influenced students' interest in the capital market through the investment gallery, (2) investment knowledge also had a positive influence on students' interest in the capital market through the investment gallery, (3) both investment motivation and investment knowledge simultaneously influenced students' interest in the capital market through the investment gallery.